2019
DOI: 10.1155/2019/9456861
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Mechanical Properties of Cemented Paste Backfill under Different Gradations of Aggregate Particles and Types and Contents of Cementing Materials

Abstract: Obtaining the optimal gradation of aggregate particles is beneficial for improving the strength of cemented paste backfill (CPB). Consequently, the uniaxial compression tests with acoustic emission (AE) monitoring were performed on CPB, for which the aggregate particles satisfied the Talbot grading theory. The effects of the Talbot indices of aggregate particles and types and contents of cementing materials on the mechanical properties of CPB were analyzed. The AE characteristics and stress-strain behaviors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The size and content of aggregates have a significant impact on porosity and the interfacial transition zone (ITZ) [8]. The overall surface area of the aggregate is determined by the particle size [9], which in turn affects the paste film thickness and water film thickness [10]. A larger aggregate surface area results…”
Section: Introductionmentioning
confidence: 99%
“…The size and content of aggregates have a significant impact on porosity and the interfacial transition zone (ITZ) [8]. The overall surface area of the aggregate is determined by the particle size [9], which in turn affects the paste film thickness and water film thickness [10]. A larger aggregate surface area results…”
Section: Introductionmentioning
confidence: 99%
“…As a porous medium consisting mainly of cementing materials, waste rock aggregate, and pores [11], the AE characteristic of CPB is closely related to the choice and the ratio of cementing material, and the aggregate particle size grading, etc. [12][13][14]. Many types of researches indicated that the loading rate has a significant effect on the properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…To study the variation of internal stress and the associated influencing factors, extensive laboratory experiments and in-situ monitoring programs have been conducted. For example, previous laboratory studies [16][17][18][19][20] have found that curing stress, water drainage, and structural filling properties (e.g., filling rate and sequences, filling time, filling interval time, and filling surface angle) affect the evolution of material properties (e.g., coefficient of permeability, shear strength parameters, elastic modulus, and so on) and the internal stress in CPB. Moreover, field monitoring programs have been carried out to assess the evolution of PWP [21] and total stress [22] in stopes with various mixture recipes and field conditions.…”
Section: Introductionmentioning
confidence: 99%